#TITLE_ALTERNATIVE# - YAN HENDRAYANA( NIM 12305007) pembimbing : Dr. Hendra Grandis ; Edi Suhanto, S.Si., M.T., YAN
Geothermal exploration is carried out to know the potential of geothermal energy in a geothermal prospect area. Geothermal exploration with geophysical methods mainly employs magnetotelluric method. This method use electromagnetic fields which go into the subsurface of the earth with the natural signal sources. Analysis on these electromagnetic fields can be used to obtain the resistivity structure beneath the earth's surface. Data processing which followed with modelling inversion is performed to obtain subsurface resistivity structure model at the geothermal prospect area in the Mount "X". Mode in the inversion of that used for 1-D model is the TE mode and 2-D model is a combination of TE mode and TM mode. The result of this inversion can be described the allegation of faults that is sealing and cap and reservoir